2014
DOI: 10.1016/j.jglr.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro phenotypic differences between Great Lakes VHSV genotype IVb isolates with sequence types vcG001 and vcG002

Abstract: Viral hemorrhagic septicemia virus (VHSV) is an aquatic rhabdovirus first recognized in farmed rainbow trout in Denmark. In the past decade, a new genotype of this virus, IVb was discovered in the Laurentian Great Lakes basin and has caused several massive die-offs in some of the 28 species of susceptible North American freshwater fishes. Since its colonization of the Great Lakes, several closely related sequence types within genotype IVb have been reported, the two most common of which are vcG001 and vcG002. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The objective of our investigation is to analyze the relative evolutionary and biogeographic differentiation patterns of VHSv-IVb among different genes over temporal and spatial distribution in the Great Lakes, building on some prior knowledge of its glycoprotein ( G -) gene variability [ 2 , 6 ]. Studies have indicated that some VHSv-IVb G -gene variants differ in their relative virulence [ 8 ]. Swift differentiation of genetic variants may allow the virus to evade host immune responses, persist in populations, and spread to new areas and hosts [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of our investigation is to analyze the relative evolutionary and biogeographic differentiation patterns of VHSv-IVb among different genes over temporal and spatial distribution in the Great Lakes, building on some prior knowledge of its glycoprotein ( G -) gene variability [ 2 , 6 ]. Studies have indicated that some VHSv-IVb G -gene variants differ in their relative virulence [ 8 ]. Swift differentiation of genetic variants may allow the virus to evade host immune responses, persist in populations, and spread to new areas and hosts [ 2 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies observed similar trends. For example, Imanse et al [ 43 ] examined vcG001 (C03MU) and vcG002 (not included in our analysis), finding faster growth but lower titers in cells exposed to vcG002. These had similar levels of viral RNA, suggesting that vcG002 was less efficient at producing infective particles.…”
Section: Discussionmentioning
confidence: 84%
“…1 μl of each cDNA was tested using RT-qPCR, with 5 μl of the Radiant Green Lo-ROX 2X qPCR kit (Alkali Scientific), 50 ng of each oligonucleotide, and water to total 10 μl. Primers used were: VHSV-Nse/as, EPC IFN se/as, and β-actin se/as [ 43 ]. Reactions and data collections were performed on a C1000 Real Time Thermocycler (Bio-Rad), with initial 3 min denaturation at 95°C, followed by 40 cycles of 15 s at 95°C, and 30 s elongation at 60°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies observed similar trends. For example, Imanse et al [44] 606 examined vcG001 (C03MU) and vcG002 (not included in our analysis), finding faster growth 607 but lower titers in cells exposed to vcG002. Those had similar levels of viral RNA, suggesting 608 that vcG002 was less efficient at producing infective particles.…”
Section: Differences In Cytopathogenicity 590mentioning
confidence: 81%